2018
DOI: 10.2147/cia.s183276
|View full text |Cite
|
Sign up to set email alerts
|

The effects of an empowering self-management model on self-efficacy and sense of coherence among retired elderly with chronic diseases: a randomized controlled trial

Abstract: BackgroundBeing elderly and retired are related phenomena that overlap in a time symmetry. The present study aimed to assess the effect of an empowering self-management model on the self-efficacy and sense of coherence (SOC) in retired elderly with chronic diseases.MethodsA randomized controlled trial that included 60 elderly people was carried out in Bushehr (Iran) in 2016. The participants were randomly assigned to either a control group or an intervention group. Based on an empowering self-management model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 37 publications
1
51
0
4
Order By: Relevance
“…While five studies evaluated on health education interventions related to self-management [43][44][45][46][47], three studies focused on exercise training interventions [48][49][50] and one study evaluated an intergenerational program involving older adults to read picture books to children [51]. Among the five health education interventions, four of them yielded promising findings in enhancing SOC of older adults [43][44][45]47]. The three exercise training interventions differed in the duration of intervention, ranging from 12 [50], 24 [48] and 36 weeks [49].…”
Section: Interventions Enhancing Socmentioning
confidence: 99%
See 2 more Smart Citations
“…While five studies evaluated on health education interventions related to self-management [43][44][45][46][47], three studies focused on exercise training interventions [48][49][50] and one study evaluated an intergenerational program involving older adults to read picture books to children [51]. Among the five health education interventions, four of them yielded promising findings in enhancing SOC of older adults [43][44][45]47]. The three exercise training interventions differed in the duration of intervention, ranging from 12 [50], 24 [48] and 36 weeks [49].…”
Section: Interventions Enhancing Socmentioning
confidence: 99%
“…Drawing attention to the health education interventions, the authors identified two common characteristics of the four interventions which yielded significant post-test SOC improvements [43][44][45]47]. These two characteristics might shed some light on SOC-enhancing strategies.…”
Section: Interventions Enhancing Socmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that different individual and contextual aspects, such as age and expected retirement age [ 8 , 39 ], gender [ 41 , 42 ], health [ 43 ], financial situation [ 44 ], job involvement/centrality [ 3 , 45 ], and psychological aspects/resources [ 7 ] can affect retirement planning/preparation. In particular, in term sof personal resources, some empirical studies showed that the first order factors (i.e., self-efficacy, self-esteem, internal locus of control, and emotional stability) included in the core self-evaluations significantly affected retirement-related outcomes.…”
Section: Core Self-evaluations Affecting Retirement-related Outcommentioning
confidence: 99%
“…Community and individual empowerment are one of the key health promotion principles stated in the Ottawa Charter for health promotion that focuses on enabling people to exercise more control over their health, environment and health choices [58]. Besides, an intervention study using an empowering selfmanagement model that focused on selfawareness, goal setting, planning, adjusting physical, psychological and social structures, and evaluation was found to improve self-efficacy and sense of coherence among elderlies with chronic diseases [59]. In particular, selfefficacy is strongly related to the competence component of the empowerment concept, and it plays a critical role in the initiation and maintenance of positive behaviour change and is a vital mechanism for effective self-management [39,60,61].…”
Section: Use Of Self-efficacy In Health Promotion Among Patients Withmentioning
confidence: 99%